Practical Benefits of Aspect-Oriented Programming Paradigm in Discrete Event Simulation. (28th December 2014) - Chibani, Meriem; Belattar, Brahim; Bourouis, Abdelhabib
Abstract : Aspect-oriented modeling and simulation is a new approach which uses the separation of concerns principle to enhance the quality of models and simulation tools. It adopts the separation of concerns (SOC) principle. Thus, crosscutting concerns such as processes synchronization, steady state detection, and graphical animation could be separated from simulation functional modules. The capture of crosscutting concerns in a modular way is carried out to cope with complexity and to achieve the required engineering quality factors such as robustness, modularity, adaptability, and reusability. This paper provides a summary of aspect-oriented paradigm with its usage in simulation by illustrating the main crosscutting concerns that may infect simulation systems. A practical example is given with the use of the Japrosim discrete event simulation library.